Determinants of the expenditure done by attendees at a sporting event: The case of World Padel Tour - Héctor V. Jiménez-Naranjo; José Luís Coca Pérez; Milagros Gutiérrez-Fernández; Antonio Fernández-Portillo (European Journal of Management and Business Economics (EJM&BE), 2016)
The influx of people attending sport events involves creating wealth in the environment where they are held. To understand the impacts of these events on the host community, it is necessary to analyze the main explanatory variables in relation to models of buying behavior in tourism, so as to know which variables are the ones that affect most the expenditure done by attendees at a sport event. Therefore, the objective of our research is to present a model to evaluate the influence that certain variables related to the model of consumer behavior have on the expenditure. For that, the variables have been grouped into those related to the personal characteristics of the attendee, and into those others of subjective nature related to the perceptions of those attending a sport event. The research has been based on the use of Structural Equation Models using the technique of Partial Least Square (PLS). The sport event that has been analyzed is the Padel tournament 'Cáceres International Open'. The proposed model shows significant results to support the relationships contained in the hypotheses, and provides positive data regarding the predictive relevance of the model.
Keywords: L83; G14; C51; 650; PLS; Sport event; Sport tourism; Structural model; World Padel Tour